Gambaran Asupan Vitamin Sebagai Zat Antioksidan Atlet Sepakbola di Pusat Pendidikan dan Latihan Pelajar Jawa Tengah di Salatiga - Ana Fitriana; Ali Rosidi; Tiurma Ria Pakpahan (Universitas Muhammadiyah Semarang, 2014)
Oxygen refreshment increased a lot during training, which led to an increase in free radical formation. The body will fight the free radicals increase the antioxidant defense system. Free radicals are formed during chronic training may exceed the capacity of antioxidant protection system, will create immunity to disease and injury decreases. Therefore we need vitamins as antioxidants. The purpose of this research is describing antioxidant vitamin intake at PPLP football athletes, Central Java Province. Type of this research is descriptive. The methods used is food weighing and food records. All the athletes at PPLP Central Java are taken as population researched. While the sample is taken in PPLP football athletes in Salatiga, Central Java, as many as 35 people. In the study will examine the intake of vitamin A , C and E as antioxidants. The results of the research shown that 74,2 % of the football athletes are 16th and 17th years old, found 15 men (42.9%) had a deficit of vitamin A, all athletes consumed enough vitamin C in the category and all athletes still have a deficit of vitamin E. Food standard held by food manager include vitamin A, C and E should be achieve athletes nutrition requirement. And doing counseling about nutrition knowledge include vitamin A, C and E for athletes.